DOI: 10.11606/t.5.2012.tde-30072012-080321
|View full text |Cite
|
Sign up to set email alerts
|

Análise de dados de pacientes internados por insuficiência cardíaca descompensada - impacto sobre desfechos clínicos e custos

Abstract: 2012 À minha maior incentivadora, minha esposa

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
2

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
1
0
2
Order By: Relevance
“…O estudo de Abuhab (2012) (21) realizado no Hospital das Clínicas de São Paulo e analisou o custo médio das internações em pacientes com insuficiência cardíaca, apontando um valor médio de internação de R$ 4.450,00. Apesar do nosso estudo não se remeter a uma patologia especifica, o gasto médio referido pelo estudo do Hospital das Clínicas é três vezes maior quando comparado aos gastos das internações em média e alta complexidade nos hospitais do estado do Rio Grande do Norte.…”
Section: Discussionunclassified
“…O estudo de Abuhab (2012) (21) realizado no Hospital das Clínicas de São Paulo e analisou o custo médio das internações em pacientes com insuficiência cardíaca, apontando um valor médio de internação de R$ 4.450,00. Apesar do nosso estudo não se remeter a uma patologia especifica, o gasto médio referido pelo estudo do Hospital das Clínicas é três vezes maior quando comparado aos gastos das internações em média e alta complexidade nos hospitais do estado do Rio Grande do Norte.…”
Section: Discussionunclassified
“…Abuhab, in 2012, analyzed data of 577 HF-related hospitalizations and found an in-hospital mortality rate of 24.0% among patients with LVEF > 45%, which was significantly lower than in patients with LVEF ≤45% (34.0% for LVEF 30-45 % and 41% for LVEF <30%). 19 Reis et al, in 2013, followed 138 patients with HFpEF (44.2% with Chagas disease) for one year and found that mortality rate (10.2%) among patients with HFpEF was significantly lower than in patients with systolic dysfunction (23.6%). 14 D'Almeida et al, in 2018, 17 conducted a randomized study with inpatients evaluating the effects of aggressive fluid and sodium restriction on decompensated HFpEF.…”
Section: Review Articlementioning
confidence: 99%
“…The possibility of adaptations of the heart is generated, being a chronic condition, which can allow a prolonged life, sometimes with some limitation to its carriers, if treated correctly. 22 It becomes the correct diagnosis of HF that is fundamental for the therapeutic and prognostic. 1 It is pointed out that, for the functional classification, the New York Heart Association -NYHA classifications (49.1%) were adopted and recorded in the records of the elderly in this study.…”
Section: Clinical Evolution In the Icumentioning
confidence: 99%